“A spirit of cabal and insubordination” : tax resistance and revolt at the end of the Dutch East India Company’s rule of the Cape Colony, 1787 – 1803 - Burger, Carl Christiaan (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.